Assessing Dentinal Microcracks in Molar Root Canals Following Preparation with OneShape, 2Shape, and OneCurve Rotary Files: An In Vitro Micro-CT Study - Shantiaee, Yazdan; Sojodi, Hooman; Zandi, Babak; Shantiaee, Kourosh; Mirzaei, Arezoo; Sayyari, Maryam (Journal of Dental School, 2025)
Objective(s): Microcrack formation during endodontic treatment is a major concern because it can compromise the success of the procedure. Although rotary nickel-titanium files have become the standard of care for canal shaping, there is some concern that they may be more likely to cause microcracks than other types of files. This study evaluated the incidence of microcracks in mandibular and maxillary molars after using three different rotary file systems. Methods: This in vitro experimental study investigated 51 canals in 30 periodontally compromised mandibular and maxillary molars. Prior to root canal instrumentation, micro-computed tomography (micro-CT) imaging was conducted. The canals were subsequently categorized into three groups (N=17), prepared using the OneShape, 2Shape, and OneCurve rotary file systems; and re-evaluated using micro-CT. Statistical analysis was performed using the Shapiro-Wilk and Levene’s tests. Intergroup comparisons were conducted using ANOVA with Tukey’s honestly significant difference (HSD) post-hoc tests. Categorical data were analyzed using chi-square tests at p<0.05. Results: There was a statistically significant difference in the mean number of microcracks after canal preparation among the groups (p = 0.02). A statistically significant increase in crack formation was observed in the OneShape group compared to both the OneCurve group (p < 0.001) and the 2Shape group (p < 0.001). Conclusion: During canal preparation, rotary files can lead to the development of dentinal microcracks. OneShape rotary files caused a higher incidence of microcracks than the 2Shape and OneCurve files.